2021
DOI: 10.3389/fcvm.2021.688513
|View full text |Cite
|
Sign up to set email alerts
|

Label-Free Multiphoton Microscopy for the Detection and Monitoring of Calcific Aortic Valve Disease

Abstract: Calcific aortic valve disease (CAVD) is the most common valvular heart disease. CAVD results in a considerable socio-economic burden, especially considering the aging population in Europe and North America. The only treatment standard is surgical valve replacement as early diagnostic, mitigation, and drug strategies remain underdeveloped. Novel diagnostic techniques and biomarkers for early detection and monitoring of CAVD progression are thus a pressing need. Additionally, non-destructive tools are required f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 121 publications
(249 reference statements)
0
3
0
Order By: Relevance
“…This includes mitochondrial fragmentation, mitochondrial dysfunction (such as excessive ROS accumulation), reduction of mitochondrial membrane potential, and mitochondrial metabolic disorders, such as the obvious downregulation of glutathione metabolism and the tricarboxylic acid (TCA) cycle. The study of Tandon et al [ 8 ] showed that changes in mitochondrial morphology may lead to the accumulation of collagen matrix in valve interstitial cells (VICs), which can be used as an index to evaluate early CAVS. The study of Morciano et al [ 9 ] showed that mitochondrial dysfunction can promote the synthesis of collagen matrix and alkaline phosphatase of VICs and accelerate the calcification process of CAVS.…”
Section: Introductionmentioning
confidence: 99%
“…This includes mitochondrial fragmentation, mitochondrial dysfunction (such as excessive ROS accumulation), reduction of mitochondrial membrane potential, and mitochondrial metabolic disorders, such as the obvious downregulation of glutathione metabolism and the tricarboxylic acid (TCA) cycle. The study of Tandon et al [ 8 ] showed that changes in mitochondrial morphology may lead to the accumulation of collagen matrix in valve interstitial cells (VICs), which can be used as an index to evaluate early CAVS. The study of Morciano et al [ 9 ] showed that mitochondrial dysfunction can promote the synthesis of collagen matrix and alkaline phosphatase of VICs and accelerate the calcification process of CAVS.…”
Section: Introductionmentioning
confidence: 99%
“…Thirdly, sections for MPM imaging could be obtained while H&E staining was routinely performed in the pathology laboratory, so the evaluation of clinical samples using the new method could be completed in the laboratory. Currently, MPM had been widely used in various diagnosis studies including dermatology, oncology, neurology, and cardiovascular disorders, and was expected to become a powerful clinical diagnostic tool [ 26 , 45 - 48 ]. In 2007, König et al reported the first clinical application of two-photon microendoscopy in detecting the extracellular matrix collagen and elastin in the dermis of patients with ulcers [ 49 ].…”
Section: Discussionmentioning
confidence: 99%
“…Second harmonic generation (SHG) microscopy is a nonlinear optical technique that has been used to analyze collagen organization for a broad range of biomedical research applications including skin biomechanics and aging [1,2], ovarian cancer [3] and cardiovascular disease [4]. One key advantage of SHG microscopy is the ability to nondestructively quantify the three-dimensional (3D) organization of collagen fibers due to its intrinsic depth-sectioning capabilities.…”
Section: Introductionmentioning
confidence: 99%